2002
DOI: 10.1093/ei/40.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Collusion in Procurement Auctions: An Experimental Examination

Abstract: Experimental methods are used to examine the existence and detectability of collusion in environments that exhibit critical parallels to procurement auctions. We find that, given the opportunity, sellers often raise prices considerably. Moreover, non-collusive Nash equilibrium predictions are insufficient to dismiss "suspicious" behavior as innocuous: In an environment where identical prices are predicted in a non-collusive Nash equilibrium, common prices are observed only when sellers communicate. In a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Hence, in that case, supra-competitive prices are frequently accompanied by price matching. From the figure and Table 3 we see that in SimEqual, Follower50 12 This has also been found in different contexts by Mason et al and Dugar and Mitra (2013) who also found that cooperation decreases over time. 13 There are a few markets where subjects manage to take turns in supplying the market by alternating in prices.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, in that case, supra-competitive prices are frequently accompanied by price matching. From the figure and Table 3 we see that in SimEqual, Follower50 12 This has also been found in different contexts by Mason et al and Dugar and Mitra (2013) who also found that cooperation decreases over time. 13 There are a few markets where subjects manage to take turns in supplying the market by alternating in prices.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…12 Second, we consider the incidence of price coordination. This is the percentage of markets where, in a given round, both subjects charge the same collusive price p C ∈ {4, 5, .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this context Isaac and Walker (1985) observed collusion in some but not all of their four-seller markets, and Davis and Holt (1998), investigating the effects of secret discounts in a three-seller and three-buyer design, found successful price-fixing in their baseline treatment without discounts. Davis and Wilson (2002) find that communication between sellers will increase cartel effectiveness.…”
Section: Introductionmentioning
confidence: 94%
“…Previous experimental research suggests that the type of trading institution employed can prominently affect pricing behavior (e.g., Plott and Smith, 1978). Furthermore, a well-established experimental research program studies pricing behavior within the context of a particular market institution (see, for instance, Alger, 1987;Cason and Davis, 1995;Davis and Wilson, 2002;Friedman and Hoggatt, 1980) and seems to suggest that environmental details play an important role. This paper falls more closely into this second strand of literature, in that we keep fixed the trading institution and we focus on factors that might facilitate collusion.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison (1987) employed a random tie-breaking rule in a study of contestable markets. Tie-breaking rules have been introduced as treatment variables by Davis and Wilson (2002) in a variant of posted-offer trading rules appropriate to a procurement auction environment. In their experiment, every market lasts for 40 trading periods and consists of 4 sellers.…”
Section: Introductionmentioning
confidence: 99%